Maintenance Procedures and Practices for Underground Mobile Mining Equipment - Mkemai, Rashid (2011)
Worldwide, underground mines mobile equipments are the most critical units in the mine production systems to ensure continuous flow of ore. Mining companies face challenges in reduction of operational cost, capital cost and maintaining high production level in this world of fast dynamic technological advancement, equipments/systems enormousness and complexity as well as ongoing attempts to automate production equipments. High equipments availability, safety, maintainability and controllable reliability become an important issue. This thesis focuses on maintenance procedures and practices for mobile mining equipment in the context of underground mining environment with the main goal of identification of major causes of equipment breakdown, identification of maintenance problems and evaluation of computerized maintenance management system data handling at LKAB (Malmberget mine) and Barrick Gold Tanzania (Tulawaka mine) and if possibly to suggest measures for improvement. The data have been presented and the efficiency of the existing maintenance management system has been discussed and illustrated for each case study area, finally the measures for improvement have been suggested. Validerat; 20110617 (anonymous)